Grynfeltt Hernia (GH): A Rare Case of Hernia - Cardoso, VS (2023)
Grynfeltt hernia (GH) is extremely rare among all abdominal wall hernias, so both diagnosis and treatment can be challenging. Surgery, open or laparoscopic, is the only definitive treatment. We present a case of a 71-year-old woman with GH (initially misdiagnosed as a lipoma), its approach, and treatment. We performed a hernioplasty with two meshes (preperitoneal and subaponeurotic position) by an open approach: Sandwich technique. This technique is safe, feasible, and associated with no short-term complications or relapses.